2021
DOI: 10.1055/a-1475-2263
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 2019 European Society of Cardiology Risk Stratification Algorithm for Pulmonary Embolism in Normotensive Elderly Patients

Abstract: Background: The 2019 European Society of Cardiology (ESC) guidelines recommend evaluation for right ventricular dysfunction in all normotensive patients with acute pulmonary embolism (PE). We compared the predictive performance of the 2019 and 2014 ESC risk stratification algorithms and the Pulmonary Embolism Severity Index (PESI). Methods: We performed a post-hoc analysis of normotensive patients aged ≥65 years with acute PE from a prospective cohort. The primary outcome was overall mortality; secondary outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
(43 reference statements)
3
5
1
Order By: Relevance
“…One meta-analysis published in 2016 also showed the overall 30-day mortality of 11.4% (9.9–13.1%) in the high-risk PESI group [ 24 ]. These findings can be explained form the higher proportion of patients with active malignancy in our study (55%) than in the previous studies (9–21%); in addition, the proportions of active DVT and recent surgery were higher than in the previous reports [ 6 , 23 ]. Nevertheless, the data on the actual prevalence of venous thromboembolism including DVT and APE in the Southeast Asian population including Thailand are lacking.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…One meta-analysis published in 2016 also showed the overall 30-day mortality of 11.4% (9.9–13.1%) in the high-risk PESI group [ 24 ]. These findings can be explained form the higher proportion of patients with active malignancy in our study (55%) than in the previous studies (9–21%); in addition, the proportions of active DVT and recent surgery were higher than in the previous reports [ 6 , 23 ]. Nevertheless, the data on the actual prevalence of venous thromboembolism including DVT and APE in the Southeast Asian population including Thailand are lacking.…”
Section: Discussioncontrasting
confidence: 72%
“…The 30-day all-cause mortality of patients with APE in our study (19.1%) was higher than previous reports (5.9%), and for the patients with PESI class V, it was 38% vs. 17.9% [ 6 ]. Another recent study in normotensive elderly patients showed overall mortality of less than 5% [ 23 ]. One meta-analysis published in 2016 also showed the overall 30-day mortality of 11.4% (9.9–13.1%) in the high-risk PESI group [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ESC prognostic algorithm was developed for the early risk assessment of patients with APE, which represented an important step in therapeutic decision making [ 8 ]. Moor et al reported that the area under the receiver operating characteristic curve (AUC) predictive value of the 2019 ESC algorithm for 30-day mortality was 0.636 [ 18 ]. In a prospective cohort study, the risk of death in patients at “intermediate-high” and “intermediate-low” risk according to the ESC model was similar, and risk stratification in patients at intermediate risk requires further improvement [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ESC prognostic algorithm was developed for the early risk assessment of patients with APE, which represented an important step in therapeutic decision making[8]. Moor et al reported that the area under the receiver operating characteristic curve (AUC) predictive value of the 2019 ESC algorithm for 30-day mortality was 0.636 [17]. In a prospective cohort study, the risk of death in patients at "intermediate-high" and "intermediate-low" risk according to the ESC model was similar, and risk strati cation in patients at intermediate risk requires further improvement [18].…”
Section: Discussionmentioning
confidence: 99%